Художня інтерпретація жанру містерії у п’єсі Олександра Ірванця «Електричка на Великдень» - Ніколаєва, О. (Слово і Час, 2022)
Статтю присвячено проблемі новаторської рецепції у творчості Олександра Ірванця архаїчного жанру містерії. На прикладі твору «Електричка на Великдень» досліджено комплекс художніх прийомів, що дозволяють творчо трансформувати євангельський сюжет «страстей Христових» у структурі сучасної драми. Індивідуально-авторська своєрідність трактовки містеріальної матриці проаналізована в контексті художніх тенденцій, що характеризують розвиток сучасної драматургії (актуалізація міфологічного мислення, жанрова взаємодія, стильовий синкретизм). The paper focuses on the innovative reception of the archaic genre of mystery in the works by Oleksandr Irvanets. Based on the play “The Electric Train for Easter”, the researcher explores literary techniques that allow creatively transforming the gospel plot of Christ’s passions within the structure of modern drama. Special authorial interpretation of the mysterious matrix is studied in the context of complex tendencies that characterize the development of modern drama (actualization of mythological thinking, genre interaction, combination of styles). A number of modern researchers’ works give grounds for specifying the thematic and poetic features of the mystery genre. Combining mundane life with sacred meanings, O. Irvanets’ play reveals genre convergence rather than diffusion. Due to the processes of convergence, the dramatic genre becomes colorful, stereoscopic, and polyphonic. Clearly realistic techniques used in the play border on elements of the theatre of the absurd and features of the symbolist drama. The powerful tendencies of remythologization, being characteristic of the world and domestic drama of the 20th century, are noticeable in the drama “The Electric Train for Easter”, which combines elements of mystery, symbolist drama, and “drama of the absurd”. These components coexist in the artistic system of the work on the principle of genre convergence, as each of them has its corresponding plotline. The most powerful mysterious element of the work determines a special concept of time: applying a linear temporal model to everyday scenes, the author clearly fixes in the dramatic action the point of transforming the profane time into sacred, cyclical, and related to the Passion of Christ. The theme of Jesus’ suffering is introduced through the biblical intertext, organically linked to the lines of the two central characters that may be seen as the modern invariant of the dialogue between Christ and Pontius Pilate.